Análise dos esforços em edifícios altos - Camara Júnior, Vilar Fiuza da (1978)
This paper has as objective the structural analysis of buildings in which the beams and columns may have several geometrical shapes and any relative position in each story. The skeletons may have elastic supports, be under vertical and lateral loads and foundation displacements. The existence of diaphragrn slabs in each floor level is admitted. The analysis is made by the displacement method. Emphasis is given to the automatic programming for computer by developping a process for the changing-bandwidth stiffness matrix treatrnent, by using the concept of story group displacements, and by building the structural equilibrium equations divided in blocks. In the many analyzed examples, the coding showed good time and result precision performances.